Rancang Bangun Adjustable Power Supply dengan Overload Current Protection Berbasis IC LM723 - Ari Bawono Putranto; Fakhruddin Mangkusasmito; Much. Azam; Zaenul Muhlisin; Megarini Hersaputri (Faculty of Engineering and Informatics, Universitas Multimedia Nusantara, 2021)
The type of power supply that is commonly used is the adjustable power supply. Its ability to generate a varying voltage level, making it suitable for testing a wide variety of electronic circuits. A conventional protection system of this type is usually a fuse, overcurrent event occurred due to improper installation of the components and circuit design will make this protection system is active and needed replacement fuse. To eliminate the need for fuse purchases at the Instrumentation and Electronics Engineering Laboratory, Undip Vocational School, an adjustable power supply was built with an overload current protection based on the LM723 IC for an operating level of 1 ampere. The system was built as non-fuse protection current limiter. This study will describe the stages of the manufacturing and testing system. The test results show that the power supply output is linear with the coefficient of determination = 0.99 and correlation = 0.99. The system can also limit the average maximum working current of 0.95 for several variations of load resistance.